2013
DOI: 10.1097/scs.0b013e31829a8458
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Idiopathic/Rheumatoid Arthritis and Orthognatic Surgery Without Mandibular Osteotomies in the Remittent Phase

Abstract: Le Fort I osteotomy with impaction and advancement genioplasty are effective procedures for occlusal and aesthetic correction of juvenile idiopathic/rheumatoid patients. Mandibular procedures may evoke further condylar resorption with pain and functional impairment of the TMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…The risk of surgical relapse was relatively low without any significant association with rheumatic diseases, which was consistent with previous studies (Leshem et al, 2006; Pagnoni et al, 2013; Thaller et al, 1990). At the same instance, some studies have shown a higher amount of relapse ranging from 21% to 48% following BSSO mandibular advancement in patients with juvenile idiopathic arthritis who also suffered from resorptive TMJ disorders (Oye et al, 2003; Stoor et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The risk of surgical relapse was relatively low without any significant association with rheumatic diseases, which was consistent with previous studies (Leshem et al, 2006; Pagnoni et al, 2013; Thaller et al, 1990). At the same instance, some studies have shown a higher amount of relapse ranging from 21% to 48% following BSSO mandibular advancement in patients with juvenile idiopathic arthritis who also suffered from resorptive TMJ disorders (Oye et al, 2003; Stoor et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Le Fort I osteotomy with superior repositioning of the maxilla and advancement genioplasty are considered more stable than other procedures 20. In fact, these procedures have been successfully used for effective correction of juvenile idiopathic/rheumatoid patients 21. We suggest that maxillary impaction surgery with advancement genioplasty offers a good prognosis without ingravescence of PCR.…”
Section: Discussionmentioning
confidence: 89%
“…The optimistic hope is that if a patient's disease process is well controlled, the result will be stable. Unfortunately, this essentially can never be guaranteed, and therefore many "successes" end up being measured in the short term of months [125][126][127][128]. A patient with a process defined by condylar resorption electing to undergo orthognathic surgery alone must absolutely be informed that relapse is expected, TMJ pain and dysfunction are not expected to resolve, and only TMJ TJR will predictably result in long-term stability [129].…”
Section: Orthognathic Surgerymentioning
confidence: 99%